Value of surgical pilot and feasibility study protocols. Issue 8 (10th May 2019) - Fairhurst, K; Blazeby, J M; Potter, S; Gamble, C; Rowlands, C; Avery, K N L
Abstract: Background: RCTs in surgery are challenging owing to well established methodological issues. Well designed pilot and feasibility studies (PFS) may help overcome such issues to inform successful main trial design and conduct. This study aimed to analyse protocols of UK-funded studies to explore current use of PFS in surgery and identify areas for practice improvement. Methods: PFS of surgical interventions funded by UK National Institute for Health Research programmes from 2005 to 2015 were identified, and original study protocols and associated publications sourced. Data extracted included study design characteristics, reasons for performing the work including perceived uncertainties around conducting a definitive main trial, and whether the studies had been published. Results: Thirty-five surgical studies were identified, of which 29 were randomized, and over half (15 of 29) included additional methodological components (such as qualitative work examining recruitment, and participant surveys studying current interventions). Most studies focused on uncertainties around recruitment (32 of 35), with far fewer tackling uncertainties specific to surgery, such as intervention stability, implementation or delivery (10 of 35). Only half (19 of 35) had made their results available publicly, to date. Conclusion: The full potential of pretrial work to inform and optimize definitive surgical studies is not being realized. Graphical Abstract: This 10-year review of UK National Institute for Health Research (NIHR)-funded surgical pilot/feasibility study protocols shows that the full potential of pretrial work to address the uncertainties and challenges of undertaking surgical trials is yet to be realized. Misunderstanding of the application and value of pilot/feasibility work persists, with poor dissemination of work, and consequent missed opportunities for learning, study adaptation and the prevention of research waste. Future work will build on existing broad recommendations, to offer focused comprehensive guidance for clinical and trial teams designing and submitting funding applications for surgical pilot/feasibility studies. RfBP, Research for Patient Benefit; CI, chief investigator. Room for better guidance